2008
DOI: 10.1002/dvg.20473
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated P19 mouse embryonal carcinoma cells as a simple in vitro model to study the molecular regulations of mesoderm formation and axial elongation morphogenesis

Abstract: Summary Because of their capacity to give rise to various types of cells in vitro, embryonic stem and embryonal carcinoma (EC) cells have been used as convenient models to study the mechanisms of cell differentiation in mammalian embryos. In this study, we explored the mouse P19 EC cell line as an effective tool to investigate the factors that may play essential roles in mesoderm formation and axial elongation morphogenesis. We first demonstrated that aggregated P19 cells not only exhibited gene expression pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 62 publications
4
101
1
Order By: Relevance
“…These observations suggest a positive feedback loop, in which a trigger amount of exogenous Wnt3a results in the transcription of multiple other canonical Wnts that are required for gastrulation events. Similar observations have been made for Wnt3 in an embryocarcinoma model (Marikawa et al, 2008).…”
Section: Porcn Genetrap Es Cells Fail To Differentiate Into Mesoderm supporting
confidence: 76%
See 1 more Smart Citation
“…These observations suggest a positive feedback loop, in which a trigger amount of exogenous Wnt3a results in the transcription of multiple other canonical Wnts that are required for gastrulation events. Similar observations have been made for Wnt3 in an embryocarcinoma model (Marikawa et al, 2008).…”
Section: Porcn Genetrap Es Cells Fail To Differentiate Into Mesoderm supporting
confidence: 76%
“…Since our cell mixing studies had conclusively excluded the possibility that Porcn is somehow required in Wnt receiving cells, this result suggests that exogenous Wnt alone is not sufficient to activate the full downstream mesoderm differentiation pathway. It has previously been shown that Wnt3 is regulated in a positive feedback loop in differentiating P19 embryonal carcinoma cells and is further required to induce other Wnts typically expressed in the primitive streak (Marikawa et al, 2008). We suggest that addition of Wnt3a to EB cultures triggers a positive feedback loop, which results in the expression of multiple Wnt ligands required for gastrulation.…”
Section: Discussionmentioning
confidence: 89%
“…The technique described in this manuscript efficiently and reproducibly generates aggregates of mouse embryonic stem cells (mESCs) that display organized symmetry-breaking and elongation 19 , combining both the hanging drop culture described by Marikawa et al 14 and EB formation. These aggregates go on to develop axial elongations, complementing existing methods for the generation of anterior organs from ES cells such as optic cups 11 and the cerebral cortex 13 , and contain cells with identities of the three germ layers which display processes similar to those during gastrulation such as rapid cell movement 19,21 .…”
Section: Discussionmentioning
confidence: 99%
“…P19 EC cells derived from an embryo-derived teratocarcinoma in C3H/He mice are multipotent. Their cardiac [37], neuronal [38,39] differentiation and mesoderm formation/axial elongation [40] have already been demonstrated. The P19 EC cell has the capacity to differentiate in vitro in response to agents such as RA [37][38][39] and DMSO [37,40].…”
Section: Lidamycin (Ldm) Exerts Its Cytotoxicity Toward Cancer Cells mentioning
confidence: 94%
“…Their cardiac [37], neuronal [38,39] differentiation and mesoderm formation/axial elongation [40] have already been demonstrated. The P19 EC cell has the capacity to differentiate in vitro in response to agents such as RA [37][38][39] and DMSO [37,40]. Mouse EC cells as well as CSCs cultured in defined medium strongly express markers found within the inner cell mass (ICM) of the blastocyst, including stage-specific embryonic antigen 1 (SSEA1) and Oct4 [30,[41][42][43], whereas the decrease of these markers can be indicative of cellular differentiation.…”
Section: Lidamycin (Ldm) Exerts Its Cytotoxicity Toward Cancer Cells mentioning
confidence: 94%